УЛОГА СИНДИКАТА У ПОСТУПКУ ОТКАЗА УГОВОРА О РАДУ - Perić, Slobodanka P (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
Сажетак: Синдикат је самостална, демократска и независна организација запослених у коју се они добровољно удружују ради заступања, представљања, унапређења и заштите својих професионалних, радних, економских, социјалних, културних и других појединачних и колективних интереса. Аутор у раду анализира улогу синдиката у поступку отказа уговора о раду на иницијативу послодавца, односно, поступак, домашај, правне последице достављања мишљења синдиката на упозорење запосленом да су се стекли услови за отказ, указујући на минимизирање улоге синдиката у заштити права запослених у поступку отказа на иницијативу послодавца. Запослени може да затражи и приложи мишљење синдиката, односно представника запослених само на упозорење о постојању разлога за отказ, али не и на решење послодавца о отказу уговора о раду. Кључне речи: отказ од стране послодавца, упозорење, синдикат, мишљење синдиката. The Role of Trade Unions in the Procedure of the Cancellation of an Employment Contract Abstract: A trade union is an independent and democratic organization of workers, joined voluntarily to represent, promote, improve and protect employees’ professional, work-related, economic, social, cultural and other individual and collective interests. In this paper, the author analyses the role of trade unions in the procedure of the cancellation of an employment contract at the initiative of the employer, i.e. the procedure, scope and legal consequences of delivering an opinion of a trade union on the warning to an employee on the existence of grounds for dismissal. In positive labour legislation of the Republic of Serbia, an employee may deliver an opinion of a trade union he/she is a member of along with a response to a warning issued by the employer on the grounds for an employment contract cancellation under conditions prescribed by law, within the time period specified for the employee’s response to the warning. These regulations apply only in case of dismissing an employee who is a trade union member, and therefore are not mandatory if an employee is not a trade union member. The aforementioned regulations allow an uneqaul position of the employees who are not members of a trade union compared to the employes belonging to a trade union. The employer is obliged to consider the delivered opinion in terms of legal norms. Moreover, according to the interpretation of the Supreme Court of Cassation an opinion of a trade union is not binding for the employer. This further indicates a minor role of trade unions in the protection of employees. An employee may procure and deliver an opinion of a trade union, i.e. employees’ representative, only regarding a warning on the existence of grounds for dismissal, but not with regard to the decision on the termination of an employment contract. Keywords: dismissal at the initiative of the employer, warning, trade union, opinion of a trade union